Programa computacional para avaliação da velocidade de impacto do martelo no SPT - Pereira, Rebeca Araujo (2023)
This study focuses on the development of a software tool for analyzing the motion of falling objects using computer vision techniques. The software aims to provide a low-cost and user-friendly alternative to accelerometer-based methods for velocity analysis in civil engineering applications, specifically in the context of Standard Penetration Test (SPT) investigations. The research encompasses the design and implementation of the software, as well as the adaptation of a test equipment prototype for simulating SPT hammer drops. The software development process involved extensive research on computer vision, the OpenCV library, and the Python programming language. A graphical user interface (GUI) was created to facilitate the user interaction with the software. The implemented software allows users to select a video file, perform calibration to establish a size reference, define the start and end points of the object's fall, and track its motion. The software utilizes color detection to identify the object of interest, and the distance and time data are recorded throughout the fall. To evaluate the software's performance, a series of experiments were conducted using the adapted test equipment. Videos of object falls from different heights were recorded and analyzed using the developed software. The results were compared with theoretical velocities obtained from Torricelli's equation and validated against measurements obtained using the established motion analysis software, Tracker. The analysis of the results indicated a good agreement between the velocities calculated by the developed software and the Tracker software, although the latter showed slightly closer results to the theoretical values. The developed software demonstrated its potential as a cost-effective tool for velocity analysis in civil engineering applications, with potential applications in SPT testing. However, further refinements are necessary to enhance its precision and usability, such as improving object detection and addressing potential video distortions. In conclusion, this study presents the development of a software tool for motion analysis in civil engineering, specifically for SPT investigations. The software provides an accessible and practical alternative to traditional accelerometer-based methods. By harnessing computer vision techniques, the software offers a user-friendly interface and facilitates the analysis of falling object velocities. Future work may involve refining the software's features, expanding its functionality, and conducting additional validations to enhance its performance and applicability in the field of civil engineering.